Urology practice during the COVID-19 vaccination campaign. Issue 4 (November 2021) - Ficarra, Vincenzo; Novara, Giacomo; Giannarini, Gianluca; De Nunzio, Cosimo; Abrate, Alberto; Bartoletti, Riccardo; Crestani, Alessandro; Esperto, Francesco; Galfano, Antonio; Gregori, Andrea; Liguori, Giovanni; Pavan, Nicola; et al.
Introduction: The current scenario of the COVID-19 pandemic is significantly different from that of the first, emergency phase. Several countries in the world are experiencing a second, or even a third, wave of contagion, while awaiting the effects of mass vaccination campaigns. The aim of this report was to provide an update of previously released recommendations on prioritization and restructuring of urological activities. Methods: A large group of Italian urologists directly involved in the reorganization of their urological wards during the first and second phase of the pandemic agreed on a set of updated recommendations for current urology practice. Results: The updated recommendations included strategies for the prioritization of both surgical and outpatient activities, implementation of perioperative pathways for patients scheduled for elective surgery, management of urological conditions in infected patients. Future scenarios with possible implementation of telehealth and reshaping of clinical practice following the effects of vaccination are also discussed. Conclusion: The present update may be a valid tool to be used in the clinical practice, may provide useful recommendations for national and international urological societies, and may be a cornerstone for further discussion on the topic, also considering further evolution of the pandemic after the recently initiated mass vaccination campaigns.